Stress analysis of vehicle structures - Tidbury, G. H. (College of Aeronautics, 1964)
A historical review is made of the methods adopted in vehicle design. This is divided into two sections, vehicles with chassis frames and integral structures. Complete solutions have been obtained for all types of chassis frames by Erz and the results of this work are given. The simple frame structural analysis has been extended for buses, with semi-integral and integral construction. Private car structural analysis has been very approximate using pencil and paper method4 various approaches have been tried with little success. The advent of the digital computer has made the analysis of such complex structures possible and the two basic methods of ‘displacements’ and 'force’ are described. The matrix force method due to Argyris is treated in detail with a complete analysis of a simplified box van structure under idealised loading. This method has been chosen for economy in computer space and its application to a more complex structure, an integral Land Rover, is indicated. With the advent of very large computers it is probable that displacement methods will, take precedence as less work in 'choosing' the idealisation and redundant systems is involved.